Clinicopathological Factors Predisposing to No. 12a Lymph Node Metastasis in Gastric Cancer: A Prospective Cohort Analysis - Amirmohsen Jalaeefar; Habibollah Mahmoodzadeh; Mohammad Shirkhoda; Ramesh Omranipour; Seyed Rouhollah Miri; Narjes Mohammadzadeh; Arshia Zardoui; Amirsina Sharifi (Cancer Reports)
ABSTRACT Background The current standard surgical procedure for gastric cancer (GC) is gastrectomy and D2 lymphadenectomy, which includes harvesting No. 12a lymph node (LN) station. Aim The purpose of this study was to identify the clinicopathologic factors associated with No. 12a lymph node metastasis. Methods and Results Eighty‐nine patients with GC undergoing gastrectomy and D2 lymphadenectomy were included in this single‐arm prospective cohort study. Logistic regression analyses were used to clarify the correlation between No. 12a involvement and clinicopathologic characteristics. Eighty‐nine patients (66% males) with a mean age of 58.86 ± 13.06 years were included. The upper third of the stomach was the most common tumor site (43.8%). neoadjuvant chemotherapy (NAC) was administered to 77 patients (86.5%). Total gastrectomy was the most common surgical procedure (67.4%), and 49.4% of tumors were poorly differentiated. Ten patients (11.24%) had 12a LN metastasis. Patients with 12a LN involvement exhibited greater number of harvested LNs in other stations (28.5[27–39.25] vs. 25[21–30], p = 0.024) and a higher presence of LN involvement in other stations (22[11–32] vs. 0[0–4], p = < 0.001). Univariate logistic regression analysis showed that the number of harvested other nodes (OR: 1.11[1.02–1.21]), number of involved other nodes (1.23[1.11–1.37]), omental involvement (OR: 10.86[1.84–64.24.57]), lymphovascular invasion (6.90[1.37–34.70]), and perineuronal invasion (OR: 6.16[1.23–31.11]) were significantly associated with No. 12a station metastasis. However, in multivariate logistic regression, only the number of involved other nodes showed a significant association with No. 12a station metastasis (OR: 1.30[1.09–1.55]). There was no difference between patients who received NAC and who did not in terms of No. 12a involvement (p value = 0.61). Conclusion Among clinicopathologic risk factors, involvement of other lymph node stations was significantly associated with No. 12a lymph node metastasis. Therefore, No. 12a lymph node dissection should be considered in patients with advanced gastric cancer.